DESAIN SEBAGAI PENDEKATAN DALAM PENINGKATAN DAYA SAING INDUSTRI KECIL MENEHGAH PRODUK ROTAN DI CIREBON - Hadiansyah, Mahendra Nur; Wismoyo, Erlana Adli; Raja, Togar Mulya (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
The right design methods and approaches will make Small and Medium Industries (SMEs) highly competitive to compete in the local and international arena. The design development industry for SMEs products also has a sustainable impact on society as workers who have an important role in the quality of products that will be produced by the SMEs where they work. During this time, CV. Cipta Abadi is one of the SMEs in Cirebon that produces and sells products made from rattan based on orders according to designs received. As long as the Industry is operational, product designs from orders received are not allowed to be produced and resold because they do not have Intellectual Property Rights (IPR) for these product designs. This SMEs does not have a unique product that is owned as an original product of his work. This is due to budget constraints in recruiting designers or financing design services. This community service program uses a science and technology simulation method through a furniture design approach. In the process the design approach follows stages that are both theoretical and practical, namely the stages of Conceptualization, Research, Design Development, Implementation, Evaluation, Presentation. In the end the team was able to provide three original designs with proportional shapes and dimensions to maximize the volume of the inner container for the needs of the export market without compromising the aesthetic value of the product which is a factor of market attractiveness both locally and internationally. The resulting rattan product designs are also registered for their intellectual property as a form of protection for industrial designs which are the exclusive economic rights of CV. Cipta Abadi.